Surface-state-mediated electron transfer at nanostructured ZnO multipod/electrolyte interfaces - Parthasarathy, Meera; Ramgir, Niranjan S.; Sathe, Bhaskar R.; Mulla, Imtiaz S.; Pillai, Vijayamohanan K. (Journal of Physical Chemistry C, 2007)
Redox kinetics of cyanoferrate(III) species adsorbed at an n-type ZnO multipod/electrolyte interface is explored using electrochemical techniques like cyclic voltammetry and impedance spectroscopy. The electrochemical impedance results are analyzed using a fluctuating energy level model, assuming isoenergetic tunneling of majority carriers through the Helmholtz layer. A shift in the slope of Mott-Schottky plots (C-sc(-2) versus E) together with evidence from cyclic voltammetry shows that the electron-transfer process is mediated by surface states formed because of the adsorption of ferricyanide ions (as evident from the results of Fourier transform infrared spectroscopy). More significantly, the pH of zero charge (point of zero zeta potential, pzzp) of ZnO multipods is found to be 4.5 (from capacitance vs pH plots) compared to that of bulk ZnO (pH 9.5), which could be explained on the basis of a lowering in the work function of the nanostructured semiconductor and its consequent susceptibility to the formation of surface states. This is in excellent agreement with our earlier observation of ultralow threshold field emission with this material in the light of the linear dependence of pzzp with work function of the electrode material. The flat-band potential of the nanostructures is found to be 200 mV more negative than that reported for bulk n-type ZnO electrodes, indicating a higher doping density in the former. A three-dimensional mapping of charge distribution in the surface states is attempted by correlating the capacitance response of the system subjected to a sinusoidal potential modulation to the semiconductor electrode with that resulting from a systematic variation of the redox potential of the dissolved acceptor (achieved by varying the pH of the electrolyte) which further reveals the polyenergetic nature of the surface states.

Shape-dependent electrocatalytic activity of platinum nanostructures - Subhramannia, Mahima; Pillai, Vijayamohanan K. (Journal of Materials Chemistry, 2008)
Since many metallic nanostructures with different shapes exhibit unique chemical and physical properties, a systematic attempt to synthesize these shape-controlled structures for property-shape correlation remains an important challenge in contemporary materials chemistry. Main difficulties like poor shape selectivity, low yield, presence of impurity phases, difficulty of separation, etc., are exacerbated since metallic structures have high surface energies which favour lower surface areas, and consequently many synthesis strategies, including the use of hard and soft templates and external nucleating agents, are being employed along with theoretical guidelines from density functional calculations on simpler systems. One of the important application areas where these structures have gained profound attention is in electrocatalysis, where the kinetics of many structure-sensitive reactions of technological relevance have been experimentally observed to show drastic changes with shape especially in the nanosize domain, at least in one dimension. Considering their scientific and technological importance, this feature article provides an overview of the recent progress on the shape-controlled synthesis of metallic nanostructures with special emphasis on platinum, and their crucial role in the electrocatalysis of anodic reactions for polymer electrolyte fuel cells.

Synthesis of Sb-doped SnO2 nanowires and hyperbranched structures - Sathe, Bhaskar R.; Patil, Mrudula; Walke, Pravin S.; Vivek, J. P.; Lele, Ashish K.; Pillai, Vijayamohanan K.; Mulla, Imtiaz S. (Science of Advanced Materials, 2009)
Branched nanostructures of semiconducting materials are of great interest for their potential applications in optoelectronic, photonic devices and sensors. We herein describe a facile single-step chemical vapor deposition route for the synthesis of Sb-SnO2 hyperbranched nanostructures comprised of elongated nanowires with 30-40 nm diameter and 10-20 Am length. The morphology and structure has been characterized by scanning electron microscopy (SEM), transmission electron microscopy (TEM), selective area electron diffraction (SAED), and powder X-ray diffraction (XRD). Also, a possible mechanism is proposed for the growth of nanowires into the hyperbranched form on the basis of the substrate effect, the role of Au nanoparticles, and the effect of Sb doping on specific morphology evolution. Interestingly, electrical conductivity measurements as a function of temperature suggest a semiconducting behavior, despite being governed by different electron-transport mechanisms with activation energies of 0.55 and 0.17 eV, which correspond to pure SnO2 and Sb-SnO2 nanowires, respectively. A precise control over the operating parameters not only envisages custom-designed, branched structures by a simple and economical route but also offers an alternative method to the expensive and tedious nanofabrication techniques for industrial applications.
Keywords: Au Nanoparticles; chemical vapor deposition; Sb-SnO2 Hyperbranched Nanostructures

Synthesis of Rh-carbon nanotube based heterostructures and their enhanced field emission characteristics - Sathe, Bhaskar R.; Kakade, Bhalchandra A.; Kushwaha, Ajay; Aslam, Mohammed; Pillai, Vijayamohanan K. (Chemical Communications, 2010)
Selective decoration of Rh nanospheres on acid functionalized carbon nanotubes has been demonstrated using Al as a sacrificial substrate. Remarkable field emission has been observed for this heterostructure as a high current density of 170 mu A cm(-2) is generated at an ultra-low threshold of 300 V mu m(-1), compared to much smaller values for Rh nanospheres and carbon nanotubes separately.

Stabilization of graphene quantum dots (GQDs) by encapsulation inside zeolitic imidazolate framework nanocrystals for photoluminescence tuning - Biswal, Bishnu P.; Shinde, Dhanraj B.; Pillai, Vijayamohanan K.; Banerjee, Rahul (Nanoscale, 2013)
Luminescent graphene quantum dots (GQDs) are encapsulated and stabilized in Zeolitic Imidazolate Framework (ZIF-8) nanocrystals. The GQDs are well confined due to the adsorption on the growing face of the ZIF-8 nanocrystals and have a profound effect on the shape of the nanocrystals from rhombic dodecahedron to spherical. Stabilizing GQDs inside the ZIF-8 nanocrystals results in tailoring of the photoluminescence emission (ca. 32 nm, bathochromic shift) of the GQD@ZIF-8 nanocrystal composite even after 3 months of aging under normal laboratory conditions. Also the water adsorption (at STP) capacity increased for the GQD@ ZIF-8 composite as compared to the pristine ZIF-8.

Structural and catalytic properties of a novel vanadium containing solid core mesoporous silica shell catalysts for gas phase oxidation reaction - Venkatathri, N.; Pillai, Vijayamohanan K.; Rajini, A.; Raju, M. Nooka; Reddy, I. A. K. (Journal of Chemical Sciences, 2013)
A novel vanadium containing solid core mesoporous silica shell catalyst was synthesized with different Si/V ratios by sol-gel method under neutral conditions. The synthesized materials were characterized by various techniques and gas phase diphenyl methane oxidation reaction. The mesoporosity combined with microporosity are formed by incorporation of octadecyltrichloro silane and triethylamine in the catalyst and it was found out from E-DAX and BET-surface area analysis. The material was found to be nanocrystalline. Vanadium is present as V4 + species in as-synthesized samples and convert to V5 + on calcination. Most of the vanadium is present in tetrahedral or square pyramidal environment. Incorporation of vanadium in silica framework was confirmed by Si-29 MAS NMR analysis. Among the various vanadium containing solid core mesoporous silica shell catalysts, the Si/V = 100 ratio exhibited maximum efficiency towards diphenyl methane to benzophenone gas phase reaction. The optimum condition required for maximum conversion and selectivity was found out from the catalytic studies.
Keywords: diphenylmethane; Gas phase oxidation; vanadium containing solid core mesoporous silica shell

Sequential electrochemical unzipping of single-walled carbon nanotubes to graphene ribbons revealed by in situ Raman spectroscopy and imaging - John, Robin; Shinde, Dhanraj B.; Liu, Lili; Ding, Feng; Xu, Zhiping; Vijayan, Cherianath; Pillai, Vijayamohanan K.; Pradeep, Thalappil (ACS Nano, 2014)
We report an in situ Raman spectroscopic and microscopic investigation of the electrochemical unzipping of single-walled carbon nanotubes (SWNTs). Observations of the radial breathing modes (RBMs) using Raman spectral mapping reveal that metallic SWNTs are opened up rapidly followed by gradual unzipping of semiconducting SWNTs. Consideration of the resonant Raman scattering theory suggests that two metallic SWNTs with chiralities (10,4) and (12, 0) get unzipped first at a lower electrode potential (036 V) followed by the gradual unzipping of another two metallic tubes, (9, 3) and (10, 1), at a relatively higher potential (1.16 V). The semiconducting SWNTs with chiralities (11, 7) and (12, 5), however, get open up gradually at +/- 1.66 V. A rapid decrease followed by a subsequent gradual decrease in the metallicity of the SWNT ensemble as revealed from a remarkable variation of the peak width of the G band complies well with the variations of RBM. Cyclic voltammetry also gives direct evidence for unzipping in terms of improved capacitance after oxidation followed by more important removal of oxygen functionalities during the reduction step, as reflected in subtle changes of the morphology confirming the formation of graphene nanoribbons. The density functional-based tight binding calculations show additional dependence of chirality and diameter of nanotubes on the epoxide binding energies, which is in agreement with the Raman spectroscopic results and suggests a possible mechanism of unzipping determined by combined effects of the structural characteristics of SWNTs and applied field.
Keywords: density functional-based tight binding calculations; Electrochemistry; graphene; Raman spectral mapping; single-walled carbon nanotubes

Synthesis of N, F and S co-doped graphene quantum dots - Kundu, Sumana; Yadav, Ram Manohar; Narayanan, T. N.; Shelke, Manjusha V.; Vajtai, Robert; Ajayan, Pulickel M.; Pillai, Vijayamohanan K. (Nanoscale, 2015)
Graphene quantum dots (GQDs) are a promising category of materials with remarkable size dependent properties like tunable bandgap and photoluminescence along with the possibility of effective chemical functionalization. Doping of GQDs with heteroatoms is an interesting way of regulating their properties. Herein, we report a facile and scalable one-step synthesis of luminescent GQDs, substitutionally co-doped with N, F and S, of similar to 2 nm average size by a microwave treatment of multi-walled carbon nanotubes in a customized ionic liquid medium. The use of an ionic liquid coupled with the use of a microwave technique enables not only an ultrafast process for the synthesis of co-doped GQDs, but also provides excellent photoluminescence quantum yield (70%), perhaps due to the interaction of defect clusters and dopants.